Aplikasi Portal Media Sosial Menggunakan Machine Learning Dengan Algoritma Naive Bayes untuk Analisis Sentimen Publik - Juandri , Raihan Ramadhan; Pamungkas , R. Wisnu Prio; Fathurrozi , Ahmad (Journal of Students‘ Research in Computer Science, 2022)
Many organizations or agencies in Indonesia have several accounts from various social media channels such as YouTube, Facebook, Twitter, and Instagram which are intended as a means of complaining about the products or services they have. As information technology develops, social media continues to grow and requires an organization to create accounts on these channels so that it can continue to relate to the public. Problems like this make it difficult for the organization to process the sentiments conveyed by the public. Therefore, a responsive web-based management system was created that can be operated via a computer or smartphone in categorizing sentiment in the form of data into information using the Naive Bayes method which is fast and high-accuracy in classification by utilizing data sources from social media channels that are integrated in the application.